Effect of Atypical Antipsychotics on Fetal Growth: Is the Placenta Involved?. (11th July 2012) - Raha, Sandeep; Taylor, Valerie H.; Holloway, Alison C.
Abstract : There is currently considerable uncertainty regarding prescribing practices for pregnant women with severe and persistent psychiatric disorders. The physician and the mother have to balance the risks of untreated psychiatric illness against the potential fetal toxicity associated with pharmacological exposure. This is especially true for women taking atypical antipsychotics. Although these drugs have limited evidence for teratological risk, there are reports of altered fetal growth, both increased and decreased, with maternal atypical antipsychotic use. These effects may be mediated through changes in the maternal metabolism which in turn impacts placental function. However, the presence of receptors targeted by atypical antipsychotics in cell lineages present in the placenta suggests that these drugs can also have direct effects on placental function and development. The signaling pathways involved in linking the effects of atypical antipsychotics to placental dysfunction, ultimately resulting in altered fetal growth, remain elusive. This paper focuses on some possible pathways which may link atypical antipsychotics to placental dysfunction.